LO29: ILearnEM.com: a curation of quality FOAM resources to learn the fundamentals of emergency medicine. (15th May 2017) - Mungham, A.; Anjum, O.; Lo, A.; Rosenberg, H.
Abstract : Introduction/Innovation Concept: Free Open Access Medical Education (FOAM) is an emerging movement enabling crowdsourced sharing of vast amounts of medical knowledge on the web, especially in the dynamic field of emergency medicine (EM). However, the wide range of FOAM producers and the lack of organization in published FOAM content results in a challenge for learners to find quality resources that meet their educational needs. ILearnEM addresses this by curating content from popular FOAM sites to provide both new and seasoned learners with an organized, topic-structured EM curriculum.Methods: The resources on ILearnEM.com are drawn from the top 50 scoring websites on the Social Media Index (SMI), an indirect measure of quality and impact for online educational resources. The quality of each individual resource is reviewed by our curators using published Quality Checklists developed specifically for FOAM. Links to the original resources are systematically organized into core EM topics and separated into "Approach to" and "Beyond the Basics" categories.Curriculum, Tool, or Material: Since its launch in February 2016, ILearnEM.com has been distributed to the University of Ottawa medical students and residents, the Canadian CCFP-EM program directors, and through social media. Content on the website is updated every two weeks by our curators through an analysis of recent online publications from each of the top 50 SMI sites. The new resources are selected based on the level of quality and the relevance to the fundamentals of EM. Content updates are announced on social media (Twitter) to further engage learners by identifying the availability of new material.Conclusion: Based on a 10-month traffic analysis, 4234 unique visitors visited ILearnEM.com with an average of 1.9 visits/person and 10.4 pages/visit. Of those responding to an online survey (n=138, response rate=3.3%) visitors were 42.8% (n=59) residents, 29.0% medical students (n=40), 19.6% practicing physicians (n=27), and 8.7% other healthcare professionals (n=12). As one of few sites with an objective for a learner-oriented approach to curating content, ILearnEM will continue to be updated regularly based on user feedback to benefit the fast growing consumer base of medical student and resident learners.